LEADERSHIP IN THE DECENTRALISED LOCAL GOVERNMENT SYSTEM IN THE CENTRAL REGION OF GHANA - Ghartey, Adom Baisie; Baisie Ghartey, Benjamin; Essaw, David Wellington (Advances in Social Sciences Research Journal, 2016)
Effective leadership is vital for achieving the virtues of decentralisation. However, the leadership approaches regarding the behaviour of leaders and the interrelationships among leaders and followers in the decentralised local government (LG) system in most developing countries appears to be directive, instructive and prescriptive rather than involving the followers and beneficiaries in the decision-making and implementation processes. The paper examined the leadership approaches in LGs in the Central Region of Ghana. Descriptive survey design and mixed-methods were used. A sample of 989 respondents was selected from three LG areas namely; Cape Coast Metropolis (CCM), Effutu Municipality and Asikuma-Odoben-Brakwa (AOB) District using multi-stage, purposive and stratified sampling procedures. Interview guide and interview schedules were used to collect primary data from regional, district and community actors. The data were analysed using content analysis and descriptive statistics. The study revealed that leadership was perceived as a position and not an influence relationship and mixed leadership behaviours were exhibited depending on the accountability expectations of leaders and followers. Also, capabilities of leaders were based on academic qualifications, professional backgrounds and experience and not their ability to influence followers to enhance management of LGs. It was recommended that LG practitioners and civil society should raise consciousness among the leadership of the LGs to recognise leadership as an influence relationship between leaders and followers and to adopt leadership approaches that will facilitate interdependence between leaders and followers.